2009
DOI: 10.1002/hbm.20850
|View full text |Cite
|
Sign up to set email alerts
|

Specialization in the default mode: Task‐induced brain deactivations dissociate between visual working memory and attention

Abstract: The idea of an organized mode of brain function that is present as default state and suspended during goal-directed behaviors has recently gained much interest in the study of human brain function. The default mode hypothesis is based on the repeated observation that certain brain areas show task-induced deactivations across a wide range of cognitive tasks. In this event-related functional resonance imaging study we tested the default mode hypothesis by comparing common and selective patterns of BOLD deactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
137
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 50 publications
24
137
1
1
Order By: Relevance
“…Within the limitation of reverse influence (Poldrack, 2006), we might speculate that the whole-brain activation observed reflects memory (MTL), attention (dorsal ACC) and focus on bodily sensations (insula). The deactivation of the TPJ (equivalent to a higher activation during the rest epochs) is compatible with the role of this area in the "default mode network" and its deactivation during attention-demanding processes (Mayer et al, 2010).…”
Section: Discussionsupporting
confidence: 68%
“…Within the limitation of reverse influence (Poldrack, 2006), we might speculate that the whole-brain activation observed reflects memory (MTL), attention (dorsal ACC) and focus on bodily sensations (insula). The deactivation of the TPJ (equivalent to a higher activation during the rest epochs) is compatible with the role of this area in the "default mode network" and its deactivation during attention-demanding processes (Mayer et al, 2010).…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, spontaneous activity within the DMN persists across both experimental and rest conditions (Greicius and Menon, 2004). While DMN activity is clearly suppressed during a WM task, there is a substantial amount of spontaneous signal fluctuations within the DMN (Fransson, 2006;Mayer et al, 2010), indicating that the network is still active in the "deactivation mode".…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, across studies, no region has been consistently reported in both networks. In addition to the various factors noted above, the lack of clarity might relate to a failure of existing studies to take into account task-dependent variations, because the networks' neural responses are likely to vary based on factors such as stimulus type, modality, or task difficulty (19,(29)(30)(31))-which might be clarified by directly comparing DMN and SN across multiple tasks and modalities. One final limitation of the existing work is the tendency to focus solely on areas of DMN-SN overlap and to ignore any large divergences between the networks.…”
Section: Significancementioning
confidence: 99%